Landslide disaster risk analysis in Pacet District, Mojokerto Regency, East Java - Chusnaini Widiastutik; Permatasari , Devi Indah; Masniarahma , Afdilla; Firdiyansah , Aldy; Nashrullah , M Iqbal (Calamity: A Journal of Disaster Technology and Engineering, 2023)
Pacet District, Mojokerto Regency, East Java is one of the areas prone to landslides. Landslides in the area that occur can threaten lives and cause environmental damage and financial losses. This study aims to analyze the risk of landslides in Pacet District, Mojokerto Regency, East Java, and apply Early Warning System (EWS) technology based on the Internet of Things (IoT). This type of research is both qualitative and quantitative, the results of the study are based on the level of threat of landslides. Designing a landslide early warning tool is not easy to do because it has to be adapted to local situations and conditions. This program will be directed at technology transfer by implementing an Internet of Things (IoT)-based Early Warning System (EWS).